2019
DOI: 10.1111/jocn.14883
|View full text |Cite
|
Sign up to set email alerts
|

Associations between fatigue, sleep disturbance and eating style in adults with type 2 diabetes: A correlational study

Abstract: Aims and objectives:To test the hypothesis that fatigue and sleep disturbance account for a significant amount of variation in eating styles among people with type 2 diabetes (T2D). Background: Healthy eating is an important component of diabetes self-care but remains a major challenge. In people with T2D, symptoms of fatigue and sleep disturbance are pervasive. However, there is limited understanding of whether fatigue and sleep disturbance are associated with eating style in people with T2D. Design: Correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…We chose the baseline characteristics [age (Hokett and Duarte, 2019; Scullin et al, 2019), gender (Spencer, 2008), high blood pressure (Borda et al, 2019; Kumar et al, 2019), high blood lipids (Reijmer et al, 2009; Kruisbrink et al, 2017), diabetes (Margolis et al, 2019; Zhu et al, 2019), being overweight (Mora-Gonzalez et al, 2019; Yeo et al, 2019), atrial fibrillation (Takii et al, 2016; Yeung et al, 2019), smoking (Blaes et al, 2019; Cohen et al, 2019), family history of stroke (Baumann et al, 2012; Reeves et al, 2014), and history of transient ischemic attack (Takahashi et al, 2009; Sico et al, 2017)] according to previous reports indicating that these parameters would affect sleep and memory. The statistical difference for baseline characteristics was insignificant between the two groups (Table 1, p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…We chose the baseline characteristics [age (Hokett and Duarte, 2019; Scullin et al, 2019), gender (Spencer, 2008), high blood pressure (Borda et al, 2019; Kumar et al, 2019), high blood lipids (Reijmer et al, 2009; Kruisbrink et al, 2017), diabetes (Margolis et al, 2019; Zhu et al, 2019), being overweight (Mora-Gonzalez et al, 2019; Yeo et al, 2019), atrial fibrillation (Takii et al, 2016; Yeung et al, 2019), smoking (Blaes et al, 2019; Cohen et al, 2019), family history of stroke (Baumann et al, 2012; Reeves et al, 2014), and history of transient ischemic attack (Takahashi et al, 2009; Sico et al, 2017)] according to previous reports indicating that these parameters would affect sleep and memory. The statistical difference for baseline characteristics was insignificant between the two groups (Table 1, p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that unhealthy diets led to excessive dietary energy intake, extreme dietary energy restriction, protein malnutrition, and starvation ketosis, and all of these are causes of diabetes fatigue [16]. Zhu and colleagues [67] reported the causal relationship of emotional eating with fatigue in adults with type 2 diabetes, but further investigation on how psychological aspects of dietary management are associated with diabetes fatigue is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The primary findings of this study were that muscle endurance and muscle mitochondrial capacity were not different between adults with TID and controls. Previous studies have suggested that type 2 diabetes is associated with increased fatigue (reduced endurance) (2327). However, there has been less research on muscle endurance and muscle mitochondrial capacity in people with T1D.…”
Section: Discussionmentioning
confidence: 99%